1998
DOI: 10.1080/09595239800187591
|View full text |Cite
|
Sign up to set email alerts
|

Support for harm‐reduction among staff of specialized addiction treatment services in Ontario, Canada

Abstract: In a mail survey of staff of specialized addiction treatment services in Ontario, respondents from different types of services varied in their level of support for a variety of harm reduction initiatives. Across all types of services support was common for needle exchange services (82-95% in favour) and for short-term non-abstinence goals for clients with alcohol or drug problems (51-98% in favour). However, mean ratings for the effectiveness of methadone maintenance were negative or near zero, and only in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
10
1
1
Order By: Relevance
“…Despite the evidence, however, efforts to implement harm reduction strategies have met with resistance from some health care professionals [7-9], especially when dealing with individuals who are considered dependent on rather than just abusing drugs or alcohol [10]. Reasons for this resistance are varied and multifaceted.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the evidence, however, efforts to implement harm reduction strategies have met with resistance from some health care professionals [7-9], especially when dealing with individuals who are considered dependent on rather than just abusing drugs or alcohol [10]. Reasons for this resistance are varied and multifaceted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, attitudes toward needle exchange were found to be favorable among physicians who treat addictions in Rhode Island [18] and addiction treatment providers in Ontario, Canada [7,19]. In contrast, in their survey of attitudes toward moderate drinking goals among addiction treatment providers in the United States, Rosenberg and Davis [8] found that approximately 75% of reporting agencies considered nonabstinance an unacceptable treatment goal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pervasive view is effected, if not actually driven, by contemporary societal views and beliefs of mental health, so-called 'mental illness' and the individuals who experience mental health problems. Related research has repeatedly shown that nurses can be thought of as representative of the broader societal group and may well form their opinions about some mental health matters in the same way the general population does; via mass media, theological beliefs, political rhetoric and hyperbole, and other channels of (mis)information (Forman et al 2001;Ford 2010;Ogborne & Birchmore-Timney 1998). Accordingly, given the overarching, media-perpetuated, societal views of people with mental illness as violent per se (see Cutcliffe & Hannigan 2001;Edney 2004;Vermuelen 2008), the clear and documented shift towards more coercive mental health policy in recent years (see Hannigan & Cutcliffe 2002), and how some nurses apparently form their personal constructs, it may not be entirely surprising that some mental health nurses reportedly view clients as the principal cause of A/V in mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…Die Versorgungsforschung in diesem Sektor hat neben der Analyse der tatsächlichen Verbreitung von kontrollorientierten Angeboten über die Jahre auch wiederholt die Akzeptanz unter Suchtfachkräften und Entscheidern in verschiedenen Regionen untersucht (vgl. für GB: [19][20][21]; für die USA: [22][23][24]; für die CH: [25]; für NOR: [26]; für AU: [27,28]; für CAN: [29][30][31][32]). Von besonderem Interesse ist hier die aktuelle Studie von Davis und Rosenberg [24], die anknüpfend an frühere Untersuchungen [21,23] Suchtfachkräfte in den USA nach ihrer Akzeptanz gegenüber reduziertem Trinken und reduziertem Drogengebrauch als Behandlungsziel befragt haben.…”
unclassified